Impact of differing methodologies for serum miRNA-371a-3p assessment in stage I testicular germ cell cancer recurrence - Christiansen, Ailsa J.; Lobo, João; Fankhauser, Christian D.; Rothermundt, Christian; Cathomas, Richard; Batavia, Aashil A.; Grogg, Josias B.; Templeton, Arnoud J.; Hirschi-Blickenstorfer, Anita; Lorch, Anja; Gillessen, Silke; Moch, Holger; et al. (Frontiers in Oncology, 2022)
Current evidence shows that serum miR-371a-3p can identify disease recurrence in testicular germ cell tumour (TGCT) patients and correlates with tumour load. Despite convincing evidence showing the advantages of including miR-371a-3p testing to complement and overcome the classical serum tumour markers limitations, the successful introduction of a serum miRNA based test into clinical practice has been impeded by a lack of consensus regarding optimal methodologies and lack of a universal protocol and thresholds. Herein, we investigate two quantitative real-time PCR (qRT-PCR) based pipelines in detecting disease recurrence in stage I TGCT patients under active surveillance, and compare the sensitivity and specificity for each method. Sequential serum samples collected from 33 stage I TGCT patients undergoing active surveillance were analysed for miR-371a-3p via qRT-PCR with and without an amplification step included. Using a pre-amplified protocol, all known recurrences were detected via elevated miR-371a-3p expression, while without pre-amplification, we failed to detect recurrence in 3/10 known recurrence patients. For pre-amplified analysis, sensitivity and specificity was 90% and 94.4% respectively. Without amplification, sensitivity dropped to 60%, but exhibited 100% specificity. We conclude that incorporating pre-amplification increases sensitivity of miR-371a-3p detection, but produces more false positive results. The ideal protocol for quantification of miR-371a-3p still needs to be determined. TGCT patients undergoing active surveillance may benefit from serum miR-371a-3p quantification with earlier detection of recurrences compared to current standard methods. However, larger cross-institutional studies where samples are processed and data is analysed in a standardised manner are required prior to its routine clinical implementation